Wine Safety, Consumer Preference, and Human Health - Moreno-Arribas, M. Victoria; Bartolomé Suáldea, Begoña (Springer International Publishing : Imprint: Springer, 2016)
The book describes emergent investigations related to wine safety and quality, showing the relationship between these concerns and consumer preferences, with a special emphasis on the beneficial effects of wine on human health. The first part of the book describes the most relevant aspects of wine safety, emphasizing the advances offered by new technologies and biotechnological progress, as well as the impact of global climate change. The second part deals with consumer preferences, a topic little discussed in previous texts, but that has gained traction not only from the scientific point of view, but also at the industrial and social level. Finally, the last section provides an opportunity for deeper recapitulation of the beneficial effects of wine and its components on human health, including novel experimental approaches and data interpretation. From the point of view of chemical and sensory complexity,as well as human health, wine is a model product that has been the focus of extensive research, with findings over the last several years being of increasing interest to winemakers, researchers and consumers.